Formulation and In Vitro and In Silico Characterization of "Nano-in-Micro" Dry Powder Inhalers Containing Meloxicam - Petra Party; Csilla Bartos; Árpád Farkas; Piroska Szabó-Révész; Rita Ambrus (MDPI AG, 2021)
Pulmonary delivery has high bioavailability, a large surface area for absorption, and limited drug degradation. Particle engineering is important to develop inhalable formulations to improve the therapeutic effect. In our work, the poorly water-soluble meloxicam (MX) was used as an active ingredient, which could be useful for the treatment of non-small cell lung cancer, cystic fibrosis, and chronic obstructive pulmonary disease. We aimed to produce inhalable "nano-in-micro" dry powder inhalers (DPIs) containing MX and additives (poly-vinyl-alcohol, leucine). We targeted the respiratory zone with the microcomposites and reached a higher drug concentration with the nanonized active ingredient. We did the following investigations: particle size analysis, morphology, density, interparticular interactions, crystallinity, in vitro dissolution, in vitro permeability, in vitro aerodynamics (Andersen cascade impactor), and in silico aerodynamics (stochastic lung model). We worked out a preparation method by combining wet milling and spray-drying. We produced spherical, 3-4 µm sized particles built up by MX nanoparticles. The increased surface area and amorphization improved the dissolution and diffusion of the MX. The formulations showed appropriate aerodynamical properties: 1.5-2.4 µm MMAD and 72-76% fine particle fraction (FPF) values. The in silico measurements proved the deposition in the deeper airways. The samples were suitable for the treatment of local lung diseases.